2020
DOI: 10.5539/enrr.v10n3p55
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Sanitation Services and Students’ Sanitation Practices among Schools in Lagos, Nigeria

Abstract: The paucity of information on the number of accessible sanitation facilities in secondary schools in developing countries has hindered efforts in attaining sustainable development in this area. Therefore, this study was designed to bridge that gap. The cross-sectional study utilized a 4-stage sampling technique to select 386 students from schools in Badagry, Lagos. Pre-tested questionnaire and observational checklists were used to obtain data. Data were analyzed using descriptive statistics and logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Similar trends of inadequate/ unavailable school WASH facilities in other geo-political zones have been reported by Ejimogu et al [32] in Owerri, South-East Nigeria; CODE [33] in Kaduna, Northwestern Nigeria; Yusuf et al [34], in Sokoto, Northwestern Nigeria; and Sanni et al [35] Gwagwalada, North Central Nigeria. Moreover, the trend of school WASH disparities between public and private schools in this study has also been reported by several other studies in Nigeria [16,21,35,36]. This is mainly because parents of private school students typically have higher educational status and income levels.…”
Section: Availability Of School Wash Facilitiessupporting
confidence: 85%
“…Similar trends of inadequate/ unavailable school WASH facilities in other geo-political zones have been reported by Ejimogu et al [32] in Owerri, South-East Nigeria; CODE [33] in Kaduna, Northwestern Nigeria; Yusuf et al [34], in Sokoto, Northwestern Nigeria; and Sanni et al [35] Gwagwalada, North Central Nigeria. Moreover, the trend of school WASH disparities between public and private schools in this study has also been reported by several other studies in Nigeria [16,21,35,36]. This is mainly because parents of private school students typically have higher educational status and income levels.…”
Section: Availability Of School Wash Facilitiessupporting
confidence: 85%
“…Some factors that contributed to the disparity in the availability of handwash facilities between the male and female toilet blocks was the closure of some new female toilet compartments for "future use" and the school administration's lack of maintenance culture. Another contributory factor could be because male students in the study location were more likely to practice open defecation, implying that they visited the male toilet blocks less frequently (Wada et al, 2020). Even though the majority of the wash-hand stations present had water available, literature has revealed that the use of soap and water is more effective in preventing transmission of diarrhoeal diseases because it eradicates bacteria of fecal origin better than the use of only water (Burton et al, 2011).…”
Section: Availability Of Handwash Facilitiesmentioning
confidence: 99%
“…11 Besides dropping out of school, other vices resultant from poor school sanitation are absenteeism, physical harm, harassment, and stigmatization among both male and female students. [12][13][14] A study across schools in Badagry, Nigeria, reported sanitation-related challenges such as violent attacks and injuries had been experienced by a third of the students, whereas one-fifth of the respondents had lost learning hours because of inaccessibility of sanitation facilities. 14 Comparatively, women and girls are also more susceptible to harassment and violence when using public sanitation facilities.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] A study across schools in Badagry, Nigeria, reported sanitation-related challenges such as violent attacks and injuries had been experienced by a third of the students, whereas one-fifth of the respondents had lost learning hours because of inaccessibility of sanitation facilities. 14 Comparatively, women and girls are also more susceptible to harassment and violence when using public sanitation facilities. 15 Considering the dire state of sanitation in Nigeria and the significance of the student population, this study seeks to identify the sanitation-related psychosocial stressors faced by students in public and private secondary schools in a peri-urban Nigerian community.…”
Section: Introductionmentioning
confidence: 99%